KONDISI PSIKOLOGIS NARAPIDANA NARKOTIKA DI LEMBAGA PEMASYARAKATAN NARKOTIKA KLAS II KARANG INTAN, MARTAPURA, KALIMANTAN SELATAN - Hairina, Yulia; Komalasari, Shanty (Jurnal Studia Insania, 2017)
This study aims to describe the psychological condition of inmates during being in Narcotics Correctional Institution II Karang Intan, Martapura, South Kalimantan. The research method used is qualitative research. Method of taking data by using interview and observation. The main research subjects were two prisoners, HRS and BSR were supported by two informants, prison officers and counselors as a complementary source of data. From the results of research can be described psychological condition of inmates are divided into four aspects, namely cognitive aspects, affective aspects, social aspects and psychomotor aspects (behavior). The research findings can be summarized as follows, on the cognitive aspect can be described prisoners are susceptible to cognitive dysfunction this is related to the ability his perception, the ability to catch and often lose concentration, while the affective aspects of deep sadness, suspicion and excessive alertness, And anxious, to social aspects show behavior tend to withdraw from association among fellow inmates, often sat pensive and become loners or close themselves. In the psychomotor aspect can be seen from maladaptive behavior, can manisfestation in the form of behavior of sleeplessness, lack of spirit and loss of interest, even the desire to hurt until the desire to end life.